2006
DOI: 10.1042/bj20051214
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative mapping of oxidation-sensitive cysteine residues in SERCA in vivo and in vitro by HPLC–electrospray-tandem MS: selective protein oxidation during biological aging

Abstract: The selective reversible S-glutathiolation of specific SERCA (sarcoplasmic/endoplasmic-reticulum Ca2+-ATPase) cysteine residues represents a novel physiologic pathway of NO (nitric oxide)-dependent arterial smooth muscle relaxation [Adachi, Weisbrod, Pimentel, Ying, Sharov, Schöneich and Cohen (2004) Nat. Med. 10, 1200-1207]. This mechanism may be impaired through the irreversible oxidation of functionally important cysteine residues as a consequence of oxidative stress and aging. To establish whether in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 39 publications
8
89
1
Order By: Relevance
“…As TAs appear to be associated with myopathy, Serca located in the TA membrane has been suggested to be inactivated or functionally compromised (Boncompagni, Protasi & Franzini‐Armstrong, 2012). Consistent with the above, our current findings in mice, and previous findings using a rat model (Sharov, Dremina, Galeva, Williams & Schoneich, 2006), have both revealed that Serca activity decreases in an age‐dependent manner and this decrease in Serca activity is correlated inversely with increased oxidative modification, namely cysteine sulfonation and 3‐nitrotyrosine, which occurs as a consequence of oxidative stress and aging.…”
Section: Discussionsupporting
confidence: 92%
“…As TAs appear to be associated with myopathy, Serca located in the TA membrane has been suggested to be inactivated or functionally compromised (Boncompagni, Protasi & Franzini‐Armstrong, 2012). Consistent with the above, our current findings in mice, and previous findings using a rat model (Sharov, Dremina, Galeva, Williams & Schoneich, 2006), have both revealed that Serca activity decreases in an age‐dependent manner and this decrease in Serca activity is correlated inversely with increased oxidative modification, namely cysteine sulfonation and 3‐nitrotyrosine, which occurs as a consequence of oxidative stress and aging.…”
Section: Discussionsupporting
confidence: 92%
“…SR/ER Ca 2+ ATPase (SERCA) is another target of redox modifications. Oxidation of SERCA1 in skeletal muscle by peroxinitrite causes an attenuation of activity of the Ca 2+ pump (Sharov et al, 2006). On the mitochondrial side, a vast body of evidence supports the activation of the PTP by ROS in cardiac muscle (Brookes et al, 2004;Halestrap et al, 2004).…”
Section: Ros As Regulatory Signaling Factors In Cardiac and Skeletal mentioning
confidence: 99%
“…8 In the case of the sarcoplasmic reticulum (SR) calcium ATPase (SERCA), for example, oxidation at multiple cysteine residues leads to loss of function. 9 …”
Section: Superoxide Peroxide and Peroxynitritementioning
confidence: 99%